The connection between sport and recreational activities and Body Mass Index (BMI) among students - Špehar, Natalija (Array, 2012)
The level of physical activity is at its larger decline while the body weight is increasing. Both of these components represent a growing global concern all around the ‘civilized’ world. According to the World Health Organization, the lack of physical activity and being overweight are two of the three intermediate leading causes of illness, disabilities and mortality. The aim of this study was to determine the involvement of students in sport and recreational activities in their free time, to recognize if there are any gender related differences and to analyze the possible correlation with the body mass index (BMI). The research was conducted on a random sample of 745 students (568 female and 177 male) ; freshmen of undergraduate studies at the Faculty of Humanities and Social Sciences at the University of Zagreb. Descriptive statistics were used to calculate frequencies and percentage of each variable in the total population, according to respondents’ gender. T-test for independent samples determined a difference between male and female students at a significance level *p<0.05. The interdependence of current sport and recreational activity practice and BMI was analyzed using regression analysis. A total of 27.92% students (42.94% male and 23.24% female) are included in sport and recreational activities, while 70.74% of students (56.50% male and 74.82% female) do not engage in any sport or recreational activities. T-test showed a statistically significant difference between male and female students for both dependent variables: participation in sport and recreational activities (t=-5.08, p=0.000000*) and BMI (t=6.07, p=0.000000*). The results of the regression analysis (Beta=-0.04, t=- 0.87, p=0.388187, R=0.08, p<0.20991) showed no statistically significant association between BMI and the predictor variable of involvement in sport and recreational activities.